Oral Interview with Mrs. Nebolisa - Oloko, Patrick; Kibora, Ludovic (Rethinking the "Informal" and Mainstreaming African Popular Arts and Entertainment, 2021)
Oral interview with Mrs. Nebolisa of Rethinking the Informal and Mainstreaming African Popular Arts and Entertainment
Keywords: Arts; Aesthetics; Music; Scholars; African Studies; Popular Music Studies; African Music; Cultural Economy